2020
DOI: 10.1080/1343943x.2020.1794916
|View full text |Cite
|
Sign up to set email alerts
|

Factors destabilizing the control of Monochoria vaginalis by rice bran: its conflicting powers influence both suppression and promotion of germination in paddy soil

Abstract: Organic paddy rice (Oryza sativa L.) cultivation can be negatively impacted because of the weeds growth like Monochoria vaginalis. Although the rice bran application is useful in combating weed, its performance is not consistent. In this study, laboratory experiments were conducted to elucidate the effects of rice bran on the suppression and promotion of germination of M. vaginalis. Suppression experiments involved incubating mixtures of flooded soil and rice bran. This was followed by a germination experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The suppression of M. vaginalis by rice bran application is associated with chemical factors indicated by electrical conductivity (EC) increase (Nozoe et al, 2021(Nozoe et al, , 2012, as well as physical ones, namely, the settled soil volume in water (Nozoe et al, 2016). We have shown that rice bran application increased the EC of soil solution, possibly because of the increased ionic compounds from rice bran decomposition, and M. vaginalis germination suppression is increased along with the EC value (Nozoe et al, 2021(Nozoe et al, , 2012. Organic acids are generally released during rice bran or organic matter decomposition in the paddy soil.…”
Section: Introductionmentioning
confidence: 99%
“…The suppression of M. vaginalis by rice bran application is associated with chemical factors indicated by electrical conductivity (EC) increase (Nozoe et al, 2021(Nozoe et al, , 2012, as well as physical ones, namely, the settled soil volume in water (Nozoe et al, 2016). We have shown that rice bran application increased the EC of soil solution, possibly because of the increased ionic compounds from rice bran decomposition, and M. vaginalis germination suppression is increased along with the EC value (Nozoe et al, 2021(Nozoe et al, , 2012. Organic acids are generally released during rice bran or organic matter decomposition in the paddy soil.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest value was observed in treatments with rice bran followed by compost. Low germination percentage in rice bran might be because of the presence of numerous antioxidant substances which cannot be decomposed easily (Nozoe et al, 2021). Whereas, compost performs better as a soil amendment.…”
Section: Relativized Percentagementioning
confidence: 99%